Anteproyecto de Creación de Nueva Carrera: Ingeniería Electromecanica - Unt - Yenque Moncada, Jose Carlos (2017)
In the present work that follows is a preliminary project that can serve as a basis for the final project design with the objective of creating the Electromechanical Engineering career at the National University of Trujillo. This career exists in many of our neighboring countries, it is a young and very prospective career. The beginning of this project has to do with the description of the Educational Model of the UNT since it is the fundamental basis of all our careers, its conception in itself is the one that guided and guided our preliminary project. A study of Supply and Demand Analysis is presented. After studying many summers and take into account our national reality and in particular Regional will be made the possible curricular mesh of this new race within the Faculty of Engineering.